Emission of the 6300 and 5577A airglow lines of atomic oxygen in equatorial regions - Steyn, J. L.(Johannes Lodewikus) (Stellenbosch : Stellenbosch University, 2012)
In title the A of 5577A is the Angstrom symbol.